Review of fungal chitosan: past, present and perspectives in Brazil - Batista,Anabelle Camarotti de Lima (2018)
Abstract Fungal chitosan is a polymer that has been discussed and studied since 1859 in the world with great advances occurring over the years. Due to its global importance, this review aims to expose the history of the production and application of fungal chitosan in Brazil. Data collection was done at the Scielo, Sciencedirect and Pubmed databases, considering the period of the last 50 years. The inclusion criteria were articles on pure or associated chitosan and, in particular, fungal chitosan produced or applied by Brazilian research groups. At the end of the review, it was noticed a fungal chitosan very studied in different continents, and in Brazil is still used in specific and small groups. With the present work, it is expected that the diffusion of the studies will be accelerated and that potential research groups for fungal chitosan may grow through interaction with the existing ones.